Pendidikan Multikultural dalam Pengorganisasian Institusi Pendidikan - Intitsal, Amiratul Fadilah; Muadin, Akhmad; Zamroni, Zamroni (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to examine more deeply the aspects of diversity in educational institution organizations. The method used is a literature review approach. A comprehensive search strategy was carried out by searching various research journal databases. The research databases used are EBSCO, Science Direct and Wiley Online. The research criteria are (1) articles written in English and Indonesian between 2013 and 2023; (2) Articles are available in full-text form; (3) the article discusses diversity/diversity in educational organizations. Multicultural education can reduce stereotypes, misunderstandings and allow individuals to interact with others. Strategies for developing multicultural education through educational strategies, examples, and habits. In addition, multicultural education needs to implement the development of higher education systems, curriculum development, improving the quality of teaching staff, developing of education management systems, equalizing audience perceptions and developing cultural understanding and diversity of perspectives.